Violence and growth in Latin America - Gregorio Giménez Esteban (Colegio de Economistas de A Coru\~na, 2007)
This paper analyses the repercussions of the high level of criminal violence in Latin America on the economy of the countries of the region. The theoretical reflections are accompanied by an empirical study using panel data made up of sixteen countries and covering the period 1979-2001. The use of different estimation techniques -which allow the consideration of the presence of time-invariant country-specific effects and the correction of the joint endogeneity of the variables- shows that violence has had a significant negative effect on investment and economic growth.
Keywords: O40; O54; K14; 330; violence; crime; growth; Latin America; Kriminalität; Gewalt; Wirtschaftswachstum; Lateinamerika